Bearing Capacity of Pile Foundations Embedded in Clays and Sands Layer Predicted Using PDA Test and Static Load Test. (2015) - Budi, Gogot Setyo; Kosasi, Melisa; Wijaya, Dewi Hindra
Abstract: Static Load Test (SLT) is the realiable method to determine bearing capacity of pile foundations. However, SLT is relatively expensive and time consuming compared to Pile Driving Analyzer (PDA) test. Therefore PDA test becoming more populer as an alternative to predict bearing capacity of piles. This paper presents the comparation of ultimate bearing capacity of pile foundations interpreted from Static Load Test (SLT) results and that predicted from PDA tests. Davisson and Chin methods were used to determine bearing capacity of pile foundations interpreted from SLT results. Correlation between bearing capacity of piles embedded in sand and clay layer interpreted from SLT and PDA test was analyzed. The result shows that bearing capacity of piles which determined based on Static Load Test interpreted using Davisson and Chin methods exhibit relatively better agreement with the predetermined ultimate bearing capacity. Almost all records of bearing capacity of pile foundation embedded in sands layer interpreted from SLT are larger than those predicted using PDA test. While bearing capacity of piles embedded in clays predicted using PDA test varies in relatively large margin compared to that determined from SLT.